Endocan, Novel Potential Biomarker for Systemic Sclerosis: Results of a Pilot Study. Issue 5 (1st September 2015) - Bălănescu, Paul; Lădaru, Anca; Bălănescu, Eugenia; Voiosu, Theodor; Băicuş, Cristian; Dan, Gheorghe Andrei
Abstract : Background: Systemic sclerosis (Ssc) is an autoimmune disease characterized by vascular alterations of small arteries and microvessels with subsequent tissue fibrosis. Endocan is expressed by endothelial cells and associated with endothelial dysfunction; therefore it could be a potential biomarker for Ssc patients. Methods: Twenty‐one Ssc patients and 20 sex‐ and age‐matched healthy controls were recruited for the study. Serum endocan levels were determined using ELISA method in all patients and controls. Results: Serum endocan levels were superior in Ssc patients (median 2.53 (1.10–7 ng/ml)) compared with controls (0.79 (0–2 ng/ml), P < 0.05). Higher serum endocan expression was seen in diffuse Ssc subset and associated with the presence of digital ulcers and daily Raynaud's phenomenon ( P < 0.05). Higher serum endocan levels were associated with a modified Rodnan skin score >14 and longer disease duration ( P < 0.05). Values of areas under the receiver operating curves showed that serum endocan had good discriminative power for Ssc diagnosis, differentiating diffuse from limited subset type and differentiating patients with modified Rodnan skin score above and under 14 (area under curve: 0.94, 0.81, 0.75, respectively). Conclusion: The results of this pilot study suggest endocan as a potential biomarker for microvascular manifestations and complications in Ssc patients. These encouraging results could promote future prospective studies in order to determine the exact role played by endocan as a biomarker for Ssc.